PERANAN SEWANG DALAM MASYARAKAT PETANI PADI BUKIT TEMIAR DI KAMPUNG PASIK, RPS PASIK, HULU KELANTAN (International Journal of Creative Future and Heritage (TENIAT), 2014)
AbstrakSewang merupakan salah satu komponen yang sangat penting dalam budaya masyarakat Orang Asli. Iabukan sahaja sekadar bertujuan untuk keraian dan hiburan, malah lebih penting dari itu iaitu berperanansebagai satu kaedah perubahan dan medium komunikasi antara manusia dengan makhluk halus, rohnenek moyang dan semangat yang mendiami alam ini. Berdasarkan bukti etnografi, sejarah dan surveiyang dijalankan di Kampung Pasik, Hulu Kelantan, makalah ini akan membincangkan tentang aspekaspek yang terkandung dalam budaya sewang dan sejauhmanakah ia berperanan dalam masyarakatOrang Asli Temiar di Kampung Pasik, Hulu Kelantan ini.AbstractSewang plays an important role in Orang Asli sosio-cultural life. It is not only regarded as one of theirsignificance performing arts but also as an important medium of communication between human andspirits that inhabited this realm. Sewang is performed widely in the Orang Asli daily life and served asan important ritual practiced. Based on ethnographic evidence, history and surveys carried out in theTemiar settlements in Pasik, Hulu Kelantan, this paper will discuss to what extent sewang play its role inthe Temiar’s society in terms of method, meaning and functions. It is hope that the discussion will give aninsight of the significance role of sewang and enhance better understanding and awareness among us inorder to sustained it as our cultural heritage.
Keywords: Sewang, Temiar, Padi Bukit